Constructing of Unlimited Single-valued Time Scale for TDC-based Event Timers - Artyukh, Yu.; Vedin, V. (Elektronika ir Elektrotechnika, 2008)
A method of time scale extension, that allows achieving practically limitless measurement range for event timing applications and substantially reducing unwanted excessive data transfer, has been proposed. The method is based on generating specific marker events, arrival times of which, relative to some "short" time scale of the primary measurement electronic hardware (Time-to-Digital Converter IC), are transferred along with measured event arrival times (time stamps) into remote hardware or into software application. The correct mechanisms of generating and using the marker events for constructing the unlimited single-valued time scale, free of uncertainty errors, has been developed and tested. Ill. 6, bibl. 2 (in English; summaries in English, Russian and Lithuanian).